Patient and clinician engagement with health information in the primary care waiting room: A mixed methods case study - Cara Penry Williams; Kristine Elliott; Jane Gall; Robyn Woodward-Kron (SAGE Publishing, 2019)
Background. Primary care waiting rooms can be sites of health promotion and health literacy development through the provision of readily accessible health information. To date, few studies have considered patient engagement with televised health messages in the waiting room, nor have studies investigated whether patients ask their clinicians about this information. The aim of this study was therefore to examine patient (or accompanying person) and clinician engagement with waiting room health information, including televised health messages. Design and methods. The mixed methods case study was undertaken in a regional general practice in Victoria, Australia, utilising patient questionnaires, waiting room observations, and clinician logbooks and interviews. The qualitative data were analysed by content analysis; the questionnaire data were analysed using descriptive statistics. Results. Patients engaged with a range of health information in the waiting room and reportedly received health messages from this information. 44% of the questionnaire respondents (33 of 74) reported watching the television health program, and half of these reported receiving a take home health message from this source. Only one of the clinicians (N=9) recalled a patient asking about the televised health program. Conclusions. The general practice waiting room remains a site where people engage with the available health information, with a televised health 'infotainment' program receiving most attention from patients. Our study showed that consumption of health information was primarily passive and tended not to activate patient discussions with clinicians. Future studies could investigate any link between the health infotainment program and behaviour change.